Supervisi Akademik oleh Kepala Sekolah dalam Meningkatkan Kompetensi Profesional Guru di MIN 4 Padang Pariaman - Agusrita Agusrita (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
Academic supervision is a series of activities to help teachers develop their abilities in managing the learning process for the achievement of learning objectives. This study aims to determine how the planning, implementation, and obstacles of academic supervision by the school principal in improving the professional competence of teachers at MIN 4 Padang Pariaman. This research uses a descriptive method with a qualitative approach. Data collection techniques using interviews, observation, and documentation study. Research subjects were the principal, vice-principal, and teachers. Data were analyzed using reduction, presentation, and conclusion drawing techniques. The results showed that academic supervision planning was prepared at the beginning of the new school year by involving vice principals, and teachers. The goal of planning the academic supervision of principals is the ability of teachers to manage to learn, starting from planning, implementing, and evaluating student learning outcomes. Academic supervision is carried out prior to communicating to teachers, conducted twice in one semester, or four times in one school year. The academic supervision techniques used are class visits, teacher meetings, teacher working groups, and training. Barriers to academic supervision still lack the school administration staff. The existence of external activities that are sudden, so that the supervision schedule that has been prepared previously is also disrupted. Teachers who are unable to attend the scheduled class visit. Teachers who are supervised feel scared and stiff when supervised. There are still some teachers who do not master information and communication technology.